2015
DOI: 10.5539/mas.v9n12p43
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Design of Hospitals on Hospital Hoteling, Healing Process and Medical Tourism

Abstract: The design of hospitals is extremely important; any person may spend a part of his life in a hospital. Considering human interaction with the environment, psychological aspects of design and their impact on the moods of inpatients and their companions and medical team ergonomics and performance, the process of designing hospitals becomes more complex. The design of operational spaces in hospitals lack appropriate and functional properties in this regard. This paper considers the studies on the role of architec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
(22 reference statements)
3
2
0
Order By: Relevance
“…In addition, according to the conducted study, the patient level of satisfaction decreases slightly as age increases. This finding appears to be in support of those of previous studies (Abinama & Jafari, 2015; Farmahini Farahani, Shamsikhani, & Sajadi Hezaveh, 2014), in which patients’ satisfaction levels have been observed to decrease slightly as their age increases. This effect may be caused by increasing feelings of anxiety, fear, and stress as patients become older and may feel lonely in the community.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, according to the conducted study, the patient level of satisfaction decreases slightly as age increases. This finding appears to be in support of those of previous studies (Abinama & Jafari, 2015; Farmahini Farahani, Shamsikhani, & Sajadi Hezaveh, 2014), in which patients’ satisfaction levels have been observed to decrease slightly as their age increases. This effect may be caused by increasing feelings of anxiety, fear, and stress as patients become older and may feel lonely in the community.…”
Section: Discussionsupporting
confidence: 92%
“…This result was in line with the other studies that reported that the patients who had a university degree were less satisfied than the other patients. 58,59 Regarding patient age (r = −0.277, p = 0.01), this finding was in accordance with previous studies, 56,59 which showed that the satisfaction level decreased with the increase in patients’ age. Although findings of studies conducted in some western countries explored the link between longer hospital stays and decrease in patients’ satisfaction level, 6062 in this study, the results did not find any relationship between patients’ overall level of satisfaction with the duration of the stay at wards (Table 10).…”
Section: Findings and Discussionsupporting
confidence: 89%
“…In other words, it appears that the architects and interior designers were aware of the findings of previous studies and the new trends in healthcare interior designs and used updated theories and new finishing materials to enhance the quality of the indoor environment. This result appeared to be in support of studies, 16,53,56 which found that the users of the newly built hospital were most satisfied with the indoor environment quality of the facilities.…”
Section: Findings and Discussionsupporting
confidence: 79%
“…It seems that the hospitals are the most influential factor that attracts the tourists because of high service quality. It is essential to promote the strength in terms of service quality, improving the weaknesses such as criteria on service charges and waiting time, which will ensure the uninterrupted in-flow of medical tourists (Abinama and Jafari, 2015). Destinations should also add the component of medical tourism such as the introduction of medical tourism and medical tourist and knowledge on the rules and regulations of medical tourism in the training programs of the medical and non-medical personnel.…”
Section: Introductionmentioning
confidence: 99%